APPLICATION OF REMOTE SENSING TECHNIQUES TO THE DETERMINATION OF BATHYMETRY IN COASTAL LAGOONS - Carvalho Junior, Oldemar (Revista de Estudos Ambientais, 2008)
The use of remote sensing as a source of information about coastal resources has been extensively explored.At the same time, remote sensing techniques have proven to be an important instrument in the planning, conservation, managing and monitoring of coastal resources. This paper discusses the determination of bathymetry of a coastal lagoon applying remote sensing techniques, using the Conceição Lagoon as a case study. The Conceição Lagoon is a coastal lagoon located at the eastern border of Santa Catarina Island, Brazil, at latitude 27º34’ S and longitude 48º27’ W. The depths were extracted from a satellite image Landsat 7 ETM+ orbit WRS 220/point 79, acquired on 07/05/2000, calibrated with field data collected in 09/10/2001. The results obtained were compared with bathymetric data of a field survey from 1989. The accuracy of the method is discussed, based on a statistical treatment of the available data. Even though the satellite and field data used for this study were not obtained at the same moment, the method proves reasonable. Suggestions for future research are noted.Keywords: Remote Sensing, depth measurements, Lagoa da Conceição, coastal management.